Best friends 1 - Sileci, Susan Banman (McGraw-Hill, 2002)
Best friends is a new six-level, content-based, integrated course for primary students, in which the presentation of the four skills inreal-life, humorous situations exposes young learners to natural language and the need to use it. Cross-curricular topics, puzzles and games, plus phonics and spelling enable children to acquire a global understanding of English and provide that special impulse to master English as a foreign language.